(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
During communication people use different forms of speech to express their thoughts according to their intends. Types of speech make the speaker`s speech to be understandable and more colorful. With different meaning speeches can do a lot of functions such as: informing, persuading, entertaining and inspiring the audience. Also, using proper types of speec increases the aesthetic impact of the speech.